1971
DOI: 10.1090/s0002-9947-1971-0274543-4
|View full text |Cite
|
Sign up to set email alerts
|

The prime radical in special Jordan rings

Abstract: Abstract. If R is an associative ring, we consider the special Jordan ring R+, and when R has an involution, the special Jordan ring S of symmetric elements. We first show that the prime radical of R equals the prime radical of R+, and that the prime radical of R intersected with S is the prime radical of S. Next we give an elementary characterization, in terms of the associative structure of R, of primeness of S. Finally, we show that a prime ideal of R intersected with S is a prime Jordan ideal of S.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1972
1972
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…As a consequence of this argument we have a simple proof for a result of Erickson and Montgomery, [1,Theorem 4].…”
Section: P(r)^bçp(r+)mentioning
confidence: 81%
See 2 more Smart Citations
“…As a consequence of this argument we have a simple proof for a result of Erickson and Montgomery, [1,Theorem 4].…”
Section: P(r)^bçp(r+)mentioning
confidence: 81%
“…We shall show (1) implies (4). If a is not strongly .R-nilpotent, then, by [1], a $ P(R). Let a0=a, then, by Lemma 2, a0Sa0^P(R).…”
Section: Theorem 3 (Erickson and Montgomery)mentioning
confidence: 93%
See 1 more Smart Citation
“…He also showed that an arbitrary simple non-commutative Jordan ring containing two nonzero idempotent whose sum is not 1 is either commutative or quasi-associative. Erickson and Montgomery [46] in 1971 observed the special Jordan ring R + , and when R has an involution and R is associative ring, the special Jordan ring S of symmetric elements. They first showed that the prime radical of R equals the prime radical of R + , and that the prime radical of R intersected with S is the prime radical of S. Also they gave an elementary characterization, in terms of the associative structure of R, of primeness of S. Finally, they proved that a prime ideal of R intersected with S is a prime Jordan ideal of S. Also, in 1971, Shestakov [218] considered the class of non-commutative Jordan rings.…”
Section: Jordan Rings(1933-2011)mentioning
confidence: 99%
“…Therefore, by the semiprimeness of R', «îXjSi = 0. H(R') = {x G R :x* = x} is a prime Jordan algebra since JR' is *-prime [5,Corollary,p. 162] and by [5,Theorem 7] «i = 0 or j3i = 0, contrary to choice.…”
Section: Let R Be An Associative Ring With Involution * and Le J A Qumentioning
confidence: 99%